THE EFFECT of Chlorella sp FLOUR FORTIFICATION on THE QUALITY of COOKIES ADDED WITH HEAD SNAKE (Channa striata) FISH PROTEIN CONCENTRATE - Sari, N Ira; ', Helwana; ', Syahrul (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This study aimed to determine the effect of Chlorella sp flour fortification on the quality of cookies added with head snake (Channa striata) fish protein concentrate with organoleptic, chemical and microbiological and to find out how many fortified Chlorella sp best in Fish Of Channa Striata protein concentrate. The method used was an experimental method and design as completely randomized design (CRD). The treatment fortification flavour Chlorella sp with consist four taraf, the taraf is C1 (Chlorella sp without flavour), C2 (2 gram Chlorella sp fortification flavour), C3 (4 gram Chlorella sp fortification flavour), C4 (6 gram Chlorella sp fortification flavour). The parameter test of the reseach is organolephtic, proximat, and coloni bacteria total.The result of the reseach is 2 gram Chlorella sp fortification flavour showed the best of the treatment, with the characteristic is green, intact and tidy (8.1), aroma slightly smelly chlorella sp (7.9), flavor tasty, savory and a little taste of chlorella sp (7.8), hollow textures and less crunchy (8.5). It contained of water 3.60%, protein 28.52%, fat 21,60%, ash 1.30% and total bacteria 3.1 x 103 Cfu / g).Keyword: Channa striata, Chlorella sp., cookies, Fish Protein Concentrate